2000
DOI: 10.18241/0073-98552014731599
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos indicadores de qualidade de laboratórios de citopatologia cervical

Abstract: Avaliação dos indicadores de qualidade de laboratórios de citopatologia cervical RESUMONeste trabalho foi avaliado o desempenho dos 13 laboratórios que realizaram o exame citopatológico para o SUS no Paraná, por meio de seis indicadores do monitoramento interno da qualidade (MIQ). Foi realizado estudo retrospectivo, baseado nos dados obtidos no programa do Ministério da Saúde, SISCOLO/CNES, dos laboratórios que efetuaram acima de 1.500 exames de Papanicolaou/ano, de janeiro de 2008 a dezembro de 2012. A avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
0
2
0
8
Order By: Relevance
“…So, when the positivity rate is very low, it is necessary to evaluate and strengthen the IQM and the quality of the data collection . In Brazil, the majority of cytopathology laboratories have positivity rates below the recommended level, indicating that they do not perform IQM properly . Bortolon et al noted that Brazilian rates are significantly lower than those observed in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…So, when the positivity rate is very low, it is necessary to evaluate and strengthen the IQM and the quality of the data collection . In Brazil, the majority of cytopathology laboratories have positivity rates below the recommended level, indicating that they do not perform IQM properly . Bortolon et al noted that Brazilian rates are significantly lower than those observed in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Esse resultado encontra-se dentro dos valores esperados e recomendados, que é de 3% a 10%, indicando um bom desempenho do processo de triagem para detecção de lesões precursoras do câncer do colo do útero. No estudo de Plewka et al 16 O percentual de HSIL avalia a capacidade do laboratório de detectar lesões precursoras do câncer do colo do útero, na tentativa de diminuir sua incidência e mortalidade 12 . Neste estudo, no período avaliado, HSIL obteve um percentual de 0,9%, mostrando-se dentro do valor preconizado que é ≥ 0,4%.…”
Section: Métodounclassified
“…Santos, M. A.; Etlinger-Colonelli, D. / Revista de Ensino, Ciência e Inovação em Saúde v. 3 n. 3 (2022) p. [25][26][27][28][29][30][31] of Hsil was 0.4%. The positivity index was at the upper reference limit (3 to 10%).…”
mentioning
confidence: 99%